Three Case Reports of Intravenous Leiomyomatosis with Intracardiac Extensions - Deng, Yundan; Song, Bing (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background Intravenous leiomyomatosis is a rare disease. Histologically, intravenous leiomyomatosis is a benign tumor, but its biological behavior can be malignant. The development of intracardiac extensions leads to congestive heart failure and occasionally sudden fatalities.Case Description The cases of three patients treated at our university between 2017 and 2018 were studied retrospectively. Intravenous tumors extending into the right heart system were fully removed without perioperative complications or death. Only one tumor recurrence was observed during the followed-up period.Conclusion The gold standard for the treatment of intravenous leiomyomatosis with intracardiac extension is complete and successful surgical resection.
Keywords: cardiovascular surgery; heart disease; tumor